ICT in the early years - Hayes, Mary.; Whitebread, David, 1948- (Maidenhead : Open University Press, 2006)
'This thought-provoking book demonstrates that the application of technology in the delivery of the curriculum is so much more than this and should give early year's educators confidence and encouragement to develop their own ideas in using ICT in innovative and imaginative ways.'--Lynn Kennington,'Early Education newsletter'. How can computers and other ICT applications be most effectively used to support learning in early years settings? Why is it important that young children use ICT in ways which are playful, creative and explorative? What research has been carried out about young children using computers and ICT, and what does this tell us?'ICT in the Early Years' carefully considers the potential of ICT to provide opportunities for young children to learn through playful and creative activities, examining research and practice in relation to the educational uses of ICT with young children. The book raises important issues about teaching in the early years using ICT, such as giving pupils control, co-operative working, access and assessment.
Cover -- TOC36;Contents -- List of figures and tables -- List of contributors -- Series editors preface -- Introduction58; Teaching for tomorrow -- CH36;Chapter 1 What do the children have to say63; -- CH36;Chapter 2 ICT58; Play and exploration -- CH36;Chapter 3 Literacy and ICT in the early years -- CH36;Chapter 4 Mathematics and ICT in the early years -- CH36;Chapter 5 Science and ICT -- CH36;Chapter 6 Creativity44; problem45;solving and playful uses of technology58; Games and simulations in the early years -- CH36;Chapter 7 Visual literacy and painting with technology58; Observations in the early years classroom -- CH36;Chapter 8 Digital animation in the early years58; ICT and media education -- CH36;Chapter 9 Using ICT to enhance the learning of music -- CH36;Chapter 10 Towards a future early years58; ICT Curriculum -- IDX36;Index -- Last Page.
Includes bibliographical references and index.
Print version record.
Keywords: Early childhood education -- Data processing; Computer-assisted instruction; Information technology -- Study and teaching (Elementary).